Deloading Algorithm for Highly Effective Suppressing Locomotive Slip and Slide - LI Jianghong; CHEN Huaguo; HU Zhaowen; XU Li; PENG Huishui (机车电传动)
Because over deloading would reduce wheel-rail adhesion utilization efficiency, it was important to determine the critical time when deloadding should be stopped. Based on wheel-rail adhesion characteristics and the dynamic model of wheel movement, this paper analyzed the variation of both wheel acceleration and vehicle traction force during the deloading and re-adhesion process, derived the optimal time for stopping slip/slide deloadding and developed the procedure for obtaining the optimal time. Experimental results show that, compared to conventional deloading schemes for restraining slip/slide, the proposed method can improve adhesion utilization up to 50%.